Structural tuning of β-enamino diketones: exploration of solution and crystalline state photochromism - Manjappa, Kiran B.; Fan, Sheng-Chieh; Yang, Ding-Yah (Frontiers in Chemistry, 2023)
A library of β-enamino diketones was prepared via base-mediated, three-component reaction of 4-hydroxycoumarins with various aromatic/aliphatic amines and β-nitrostyrenes under microwave irradiation conditions to investigate their photochemical properties. Among the prepared compounds, a thiophene derived β-enamino diketone was found to be light-sensitive and to exhibit unique photochromic behavior, that is, positive photochromism in solution and negative photochromism in crystalline phase. In addition, this prepared photochromic compound was further covalently linked to a structure-related, piezochromic β-enamino diketone moiety to explore its potential multi-stimuli responsive properties.